Characterizing screening champions in the center for disease control and prevention’s Colorectal Cancer Control Program (CRCCP) - Cam Escoffery; Juzhong Sun; Amy DeGroff; Krishna Sharma; Manal Masud; Thuy Vu; Dara Schlueter; Peggy Hannon (Implementation Science Communications)
Abstract Background CDC’s Colorectal Cancer Control Program (CRCCP) aims to increase colorectal cancer (CRC) screening prevalence by implementing evidence-based interventions (EBIs) in health system clinics partnering with the program. Program champions, as one of the key program components, are expected to facilitate the implementation of EBIs and support desired changes in many ways. Given limited information about the champions in clinical systems, this study investigated champion types, roles, and sustainability within the CRCCP. Methods This mixed methods, cross-sectional study included a survey of 205 respondents (health system and clinic staff) representing 303 clinics and 12 qualitative interviews of CRCCP award recipients and partnering clinics. The survey assessed clinic characteristics, EBI implementation, information about program champions, and sustainability. Interview topics included champion roles, benefits, turnover, and maintenance. Findings Champions worked at either the health system or clinic level. Among health systems, champions were quality improvement (QI) managers (48.5%), physicians (36.4%), or high-level administrators (27.3%). In clinics, champions were physicians (37.0%), QI managers (26.1%) or medical assistants (23.9%). Champions in both health systems and clinics were most often assigned the role (45.5% and 45.7%, respectively); yet clinic champions were more likely to naturally emerge than health system champions (26.1% vs. 15.2%). Among naturally emerging champions, 64.3% experienced zero turnover, more than for assigned champions. While champions in both groups received training, more champions in health systems reported being trained than those in clinics (75.8% vs 52.2%). No significant differences in EBIs implemented were observed between those clinics with and without a champion. Zero champion turnover was associated with great or very great leadership support (68.9%), program adaptation (60.7%) and organizational capacity (54.1%). Interviews found that champions’ roles included advocating for CRC screening, providing technical assistance for EBI implementation, creating organizational policies for CRC screening, and overseeing QI. Interviewees reported a desire to address champion sustainability. Conclusion These findings inform the use of program champions for clinic-based public health programs. Naturally emerging champions were more stable than those assigned the role.